2008
DOI: 10.1016/j.jml.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Control of access to memory: The use of task interference as a behavioral probe

Abstract: Directed forgetting and prospective memory methods were combined to examine differences in the control of memory access. Between studying two lists of target words, participants were either instructed to forget the first list, or to continue remembering the first list. After study participants performed a lexical decision task with an additional requirement to respond with a designated key to targets from one or both of the lists. List discrimination performance supported the assumption that contextual represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…PAM theory proposes that the costs are due, at least in part, to engagement of preparatory attention, which allows the individual to be prepared to make a decision to respond differently to certain stimuli (Smith et al, 2007). However, the exact nature of those processes has yet to be determined and the existence of a cost can be interpreted in different ways (for discussion see Hicks et al, 2005; Loft, Humphreys, & Whitney, 2008). Nevertheless, costs to ongoing tasks have been demonstrated in a variety of tasks (Smith et al, 2007), including the ATC task in Loft and Remington (2010) and the current experiments.…”
Section: Discussionmentioning
confidence: 99%
“…PAM theory proposes that the costs are due, at least in part, to engagement of preparatory attention, which allows the individual to be prepared to make a decision to respond differently to certain stimuli (Smith et al, 2007). However, the exact nature of those processes has yet to be determined and the existence of a cost can be interpreted in different ways (for discussion see Hicks et al, 2005; Loft, Humphreys, & Whitney, 2008). Nevertheless, costs to ongoing tasks have been demonstrated in a variety of tasks (Smith et al, 2007), including the ATC task in Loft and Remington (2010) and the current experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent findings provide additional support for this hypothesis. For example, Loft, Humphreys, and Whitney (2008) demonstrated that intentionally forgotten materials interfere more with ongoing task performance under exclusion than inclusion conditions. Also, Gottlob and Golding (2007) found directed forgetting in source monitoring, where in addition to identifying the Old/New status of the words, participants had to retrieve their case/color/list membership.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did test for memory for identity. Given recent evidence on the importance of source monitoring and inhibitory control in memory (Jacoby, Shimizu, Daniels, & Rhodes, 2005; Loft, Humphreys, & Whitney, 2008), we decided to deviate from accepted practice and test for (a) identity at source as well as for (b) memory for words. Our goal was to examine the relationship between memory for words per se (serving to derive the DFE) and memory for their source at study.…”
Section: Introductionmentioning
confidence: 99%